Регулярные прецессии гиростата с переменным гиростатическим моментом под действием потенциальных и гироскопических сил - Мазнев, А.В. (Доповіді НАН України, 2011)
Отримано умови існування регулярних прецесій гіростата під дією потенційних та гіроскопічних сил у припущенні, що величина гіростатичного моменту залежить від часу. Досліджено зв'язок цих умов з умовами існування регулярних прецесій гіростата під дією сили тяжіння. The conditions of the existence of gyrostat regular precessions under the influence of potential and gyroscopic forces supposing that the gyrostat moment depends on the time are obtained. Their connection with the conditions of the existence of gyrostat regular precessions under the influence of gravity is studied.